Longitudinal relation between negative life events and non-suicidal self-injury among Chinese college students: a moderated mediation model - Fei Yin; Wenlong Jiang; Shuhui Huo; Xi Jin; Mengtian Li; Li Liu; Jianqin Cao (BMC Psychiatry)
Abstract Background Non-suicidal self-injury (NSSI) poses a significant public health concern, characterized by its high prevalence, recurrence, and association with suicide. While prior research has identified a connection between negative life events (NLEs) and NSSI, only a few studies have longitudinally explored this relation and its underlying mechanisms. Objective Our study investigated the longitudinal association between NLEs and NSSI among Chinese college students. We also examined the mediating role of rumination and emotional regulation difficulties, as well as the moderating role of sex. Methods We recruited 4892 students from six colleges in northern China. We assessed NLEs, NSSI, rumination, and emotional regulation difficulties at baseline (T1) and after a 1-year follow-up (T2). Result The longitudinal moderated mediation model revealed that early NLEs exerted significant direct predictive effects on later NSSI and indirect predictive effects on NSSI through the independent mediation of rumination and emotional regulation difficulties, as well as a chain mediating effect through them. The first stage (predicting the effect of NLEs on NSSI) and second stage (predicting the effect of NLEs on rumination) were moderated by sex. Conclusion Our findings underscore the importance of considering recent stressors in assessing risks and implementing interventions for college students involved in NSSI. Mental health professionals should prioritize helping students develop emotional regulation skills and reduce rumination while being mindful of sex differences.